Volume Flow and Peak Systolic Velocity of the Arteriovenous Circuit in Patients after Percutaneous Deep Venous Arterialization - Michiel A. Schreve; Eline Huizing; Steven Kum; Jean-Paul P. M. de Vries; Gert J. de Borst; Çağdaş Ünlü (Diagnostics, 2020)
Percutaneous deep venous arterialization (pDVA) is a developing technique for limb salvage in patients with chronic limb-threatening ischemia by creating an arteriovenous (AV) circuit. After pDVA, patency of the AV circuit is evaluated using duplex ultrasound (DUS) imaging. Peak systolic velocity (PSV) and volume flow (VF) values for maintaining a patent AV circuit are undefined; therefore, guidance about when a reintervention should be performed is lacking. The objective of this study was to interpret post-pDVA PSV and VF values in relation to AV circuit preservation. This was performed by analyzing DUS results of 22 post-pDVA patients. A total of 670 PSV and 623 VF measurements were collected. A PSV value of ≤55 cm/s and a VF value of ≤195 mL/min were found predictive for failure. The reliability of PSV and VF measurements in patent AV-circuits was good (intraclass correlation coefficient; PSV, 0.85; VF, 0.88). In conclusion, this study is the first to analyze DUS measurements in post-pDVA patients and showed that DUS can be used to anticipate for failure. The thresholds found can be used to help interpret DUS measurements in post-pDVA patients. More research in a larger patient population is needed to prospectively validate these thresholds.